Biochar production from microalgae cultivation through pyrolysis as a sustainable carbon sequestration and biorefinery approach - Yu, Kai Ling; Show, Pau Loke; Ong, Hwai Chyuan; Ling, Tau Chuan; Chen, Wei-Hsin; Salleh, Mohamad Amran Mohd (Springer, 2018)
Microalgae cultivation and biomass to biochar conversion is a potential approach for global carbon sequestration in microalgal biorefinery. Excessive atmospheric carbon dioxide (CO2) is utilized in microalgal biomass cultivation for biochar production. In the current study, microalgal biomass productivity was determined using different CO2 concentrations for biochar production, and the physicochemical properties of microalgal biochar were characterized to determine its potential applications for carbon sequestration and biorefinery. The indigenous microalga Chlorella vulgaris FSP-E was cultivated in photobioreactors under controlled environment with different CO2 gas concentrations as the sole carbon source. Microalgal biomass pyrolysis was performed thereafter in a fixed-bed reactor to produce biochar and other coproducts. C. vulgaris FSP-E showed a maximum biomass productivity of 0.87 g L−1 day−1. A biochar yield of 26.9% was obtained from pyrolysis under an optimum temperature of 500 °C at a heating rate of 10 °C min−1. C. vulgaris FSP-E biochar showed an alkaline pH value of 8.1 with H/C and O/C atomic ratios beneficial for carbon sequestration and soil application. The potential use of microalgal biochar as an alternative coal was also demonstrated by the increased heating value of 23.42 MJ kg−1. C. vulgaris FSP-E biochar exhibited a surface morphology, thereby suggesting its applicability as a bio-adsorbent. The cultivation of microalgae C. vulgaris FSP-E and the production of its respective biochar is a potential approach as clean technology for carbon sequestration and microalgal biorefinery toward a sustainable environment.